2021
DOI: 10.1038/s41598-021-88432-z
|View full text |Cite
|
Sign up to set email alerts
|

Serine protease dynamics revealed by NMR analysis of the thrombin-thrombomodulin complex

Abstract: Serine proteases catalyze a multi-step covalent catalytic mechanism of peptide bond cleavage. It has long been assumed that serine proteases including thrombin carry-out catalysis without significant conformational rearrangement of their stable two-β-barrel structure. We present nuclear magnetic resonance (NMR) and hydrogen deuterium exchange mass spectrometry (HDX-MS) experiments on the thrombin-thrombomodulin (TM) complex. Thrombin promotes procoagulative fibrinogen cleavage when fibrinogen engages both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…24,26 This protection disappears after 10 min if a 1.5:1 TM:thrombin ratio is used. 27 Therefore, studies of protein surface protection should be carried out for short deuteration times, and interface protection will occur immediately, at the earliest time point, and will not build up over time. These features of surface protection result in an informative time window for deuterium exchange between 0 and 10 min.…”
Section: ■ Hdx-ms and Protein Surface Protectionmentioning
confidence: 99%
See 3 more Smart Citations
“…24,26 This protection disappears after 10 min if a 1.5:1 TM:thrombin ratio is used. 27 Therefore, studies of protein surface protection should be carried out for short deuteration times, and interface protection will occur immediately, at the earliest time point, and will not build up over time. These features of surface protection result in an informative time window for deuterium exchange between 0 and 10 min.…”
Section: ■ Hdx-ms and Protein Surface Protectionmentioning
confidence: 99%
“…In contrast, it is unlikely that the H-bonding state of the pathway residues will change (recall that these are minimally frustrated and well-folded regions of the protein), so HDX-MS typically reveals the end points of the allosteric pathway because it captures the changes in H-bonding and solvent accessibility at the ends of the pathway. A clear example of this is our recent study of the thrombin−TM complex by NMR and HDX-MS. 27 TM binds to the Nterminal β-barrel and allosterically reduces the dynamics of the C-terminal β-barrel (Figure 5). The 170s loop (residues 160− 189 CT ) did not show a reduction in H/D exchange upon TM binding, whereas the 220s loop (residues 212−227 CT ) did show a reduction (Figure 5B).…”
Section: ■ Hdx-ms and Protein Surface Protectionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only the recent publication of nuclear magnetic resonance (NMR) Carr−Purcell−Meiboom−Gill (CPMG) experiments measuring the dynamics of thrombin-TM456 has been able to reveal the residue-level changes in thrombin that result when TM456 binds. 21 These experiments showed that TM456 binding reduces μs−ms motions in the 170s CT , 180s CT, and 220s CT loops, which are implicated in thrombin substrate recognition and binding, and residues Trp 215 CT (263 seq ) and Glu 217 (265 seq ) were highlighted as residues that link the 170s CT and 220s CT loops through sidechain interactions. HDX-MS and accelerated MD simulations showed that mutation of residue 215 CT induced disorder and increased dynamics in the 170s CT and the 220s CT loop, 22,23 raising questions regarding the effect of the combined W215A and E217A mutations on thrombin dynamics and on the allosteric influence of TM.…”
Section: ■ Introductionmentioning
confidence: 99%